MEMBANGUN KEWIRAUSAIIAAN DALAM PERSPEKTIF AGRIBISNIS DI ERA GLOBALISASI - Fatima, Imaculata (Agriculture Faculty of Flores University, 2008)
To face the economic problems in this global era, the agriculture sector can support the needs of many people in Indonesia, particularly those who have a low economic background. Recently most farmers have worked hard to increase their productivity. However, they often find have problems or handicaps such as (1) human resource is still low; (2) financial problems; (3) land is not enough to produce commodities; (4) infrastructures are not available enough; (5) appropriate technologies are not enough; (6) networking system of agriculture is not established yet to all agriculture sector; (7) most of the farmers are depending on the natural support; (8) skill, spirit entrepreneurship and sense of self-support of the farmers are not optimized. Regarding these problems, in fact, most farmers are developing their agriculture sectors without considering the quality of their products which is very important to the consumers, the second problem is economic global which is running fast. This can cause problems for farmers. It is therefore, all the farmers should be motivated to improve their capability on agriculture and their feeling confidence. Based on the issues, this article focuses on the single problem like